2020
DOI: 10.1002/bies.202000111
|View full text |Cite
|
Sign up to set email alerts
|

Skipping sex: A nonrecombinant genomic assemblage of complementary reproductive modules

Abstract: The unusual occurrence and developmental diversity of asexual eukaryotes remain a puzzle. De novo formation of a functioning asexual genome requires a unique assembly of sets of genes or gene states to disrupt cellular mechanisms of meiosis and gametogenesis, and to affect discrete components of sexuality and produce clonal or hemiclonal offspring. We highlight two usually overlooked but essential conditions to understand the molecular nature of clonal organisms, that is, a nonrecombinant genomic assemblage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 114 publications
(209 reference statements)
0
8
0
Order By: Relevance
“…It states that the formation of ‘asexually' reproducing hybrids ( box 1 ) is particularly likely when the genetic divergence between parental genomes is large enough to distort hybrid gametogenesis towards producing a high proportion of unreduced gametes, but not too large to significantly affect hybrid viability or fertility. Discussing the balance hypothesis, Stöck et al ([ 148 ], supported by [ 149 , 150 ]), also emphasized that ‘asexual' vertebrates are very rarely formed (e.g. 0.5% of reptile species [ 39 , 151 , 152 ]) since both sufficient divergence and generally complex genetic preconditions are necessary to naturally produce viable and fertile clonal genomes and phenotypes (‘rare formation hypothesis' [ 148 ]).…”
Section: The ‘Extended Speciation Continuum'mentioning
confidence: 99%
“…It states that the formation of ‘asexually' reproducing hybrids ( box 1 ) is particularly likely when the genetic divergence between parental genomes is large enough to distort hybrid gametogenesis towards producing a high proportion of unreduced gametes, but not too large to significantly affect hybrid viability or fertility. Discussing the balance hypothesis, Stöck et al ([ 148 ], supported by [ 149 , 150 ]), also emphasized that ‘asexual' vertebrates are very rarely formed (e.g. 0.5% of reptile species [ 39 , 151 , 152 ]) since both sufficient divergence and generally complex genetic preconditions are necessary to naturally produce viable and fertile clonal genomes and phenotypes (‘rare formation hypothesis' [ 148 ]).…”
Section: The ‘Extended Speciation Continuum'mentioning
confidence: 99%
“…Apomixis is assumed to result from temporal and spatial changes in important stages of sexual development, caused by mutations or epigenetic modifications that arise after hybridization and polyploidization events [2,14,15]. As apomixis and sexuality coexist in the same plant or even in the same ovule [1,4,16], it has been proposed that apomixis emerged from the rearrangement of sexual developmental programs [17][18][19][20]. Contrary to this, other authors indicate that the main molecular components associated with apomixis (apomeiosis and parthenogenesis) may have emerged before sex [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the switch between sexuality and unisexuality occurs from one generation to another in the polyploid Carassius complex, suggesting that it might be based on genetic machinery present in the direct ancestors of the clones. Recently, Hojsgaard and Schartl (2021) proposed that a nonrecombinant genetic assemblage might be an essential condition for the occurrence of a unisexual lineage. In this study, we observed the suppression of synapsis and the first meiotic division during oogenesis of C. gibelio clone A + and wild clone H ( figs.…”
Section: Discussionmentioning
confidence: 99%
“…Over 100 species or biotypes across around 22 genera of fish, amphibians, and reptiles are able to reproduce via parthenogenesis, gynogenesis, or hybridogenesis ( Gui and Zhou 2010 ; Avise 2015 ; Zhou and Gui 2017 ). However, as an evolutionary genetic paradox, the unusual evolutionary persistence, clonal diversity, and reproductive strategy of unisexual vertebrates remain a puzzle ( Hojsgaard and Schartl 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation